A importância do ambiente virtual de aprendizagem na institucionalização da EaD em uma instituição pública: o caso do IF Goiano - Deus, Karen Brina Borges de (2025)
The subject of this study is Distance Education (DE) as a public policy and the role of the Virtual Learning Environment (VLE) in the institutionalization of this modality. This dissertation is related to the Master's degree of the Postgraduate Program in Education of the Faculty of Education of the Federal University of Goiás (PPGE/UFG), associated with the research line State, Policies and History of Education, which studies and analyzes the State, the transformations resulting from its actions in the formulation and materialization of social policies, especially educational policies. The objective of this research is to analyze the VLE as a constituent element of distance education, seeking to understand its implementation, institutionalization, institutional policies, and requirements that regulate its choice, as well as its role in the provision of distance education at the institution and its role in the provision of distance education at the Federal Institute of Education, Science and Technology Goiano (IF Goiano). The specific objectives of this study are: to learn about the history and concepts of distance education, VLE, and institutional policies for this modality; to identify the intentions, importance, and criteria for choosing VLE and its impact on the provision of distance education courses; to analyze institutional public policies for the implementation, promotion and use of VLE, as well as its role as a constituent element of distance education. The qualitative, exploratory, bibliographic, and documentary research, according to Creswell (2010), Minayo (2009), Vousgerau and Romanowski (2014), and Minayo, Deslandes and Gomes (2016), investigates the importance of continuous attention to the constituent elements of distance education, its processes, and arrangements, from implementation to full integration. For the analysis and understanding of the object, in the chapter on the institutionalization and characteristics of distance education in Brazil, the study was based on the contributions of Freire (1987), Esman and Blaise (1966), Esman (1972), Dimaggio and Powell (1983), Curry (1991; 1992), Tolbert and Zucker (1998), Sobrinho (2003), Dourado, Oliveira and Santos (2007), Dourado and Oliveira (2009), Dourado and Santos (2011), Platt (2009), Lima (2013), Lima (2014a), Lima (2014b), Peixoto (2015), Lima (2019), Fonseca (2020), Kesar and Sam (2012), Rodrigues (2021), Lima, Rodrigues and Cruz (2021), Kesar (2007), Deus, Cruz and Lima (2023), Cruz (2018, 2022) and Medeiros (2009). To explore the historical concept and materialization of the VLE as an educational platform and its materialization in educational practice, this work was based on the authors Freire (1967), DeFleur and Ball-Rokeach (1993), André (2002), Paulsen (2002), Santos (2003), Lemos (2003), Castells (2000; 2003), Leitão and Nicolaci-da-Costa (2000; 2003), Hohlfeldt, Martino and França (2001), Pereira, Schimitt and Dias (2002), Filatro (2008), Haguenauer et al. (2009), Haguenauer, Mussi and Filho (2012), Sales, Valente and Aragão (2010), Silva (2011), Santos (2006; 2016), Schmitt and Dias (2007), Ruas (2016), Belloni (2021), Clarenc (2013), Silva and Paiva (2023), Furtado and Amiel (2016), Galeffi (2011), Fonseca (2020), Rodrigues (2021), Focault (2000), Toshi (2011), Evaristo (2018), Santos and Araújo (2009), Franco et al. (2003) and Lima et al. (2024). One of the study's conclusions is that the VLE when integrated into a well-structured, standardized, and regulated institutional policy, can support and underpin the institutionalization of distance education and the goals of the Higher Education Institution (HEI). From this perspective, the VLE becomes an important tool for promoting the inclusion and education of students by stimulating their intellectual autonomy and critical awareness. However, it is important to recognize that in distance education, these benefits do not depend exclusively on the use of the VLE, as it is one of the components of distance education. The role of the VLE in distance education policy must, therefore, be clearly understood, taking into account its educational potential, its importance in the distance education ecosystem, as well as the challenges and contradictions inherent in the modality.